TOWARD A DEEPER UNDERSTANDING OF SUPPLY CHAIN RESILIENCE IN SMES: A SYSTEMATIC LITERATURE SYNTHESIS - Fiki Hidayatul Muniroh (Resilience of Small Medium Business, 2025)
Objective: This study aims to conduct a systematic literature review to deepen understanding of supply chain resilience (SCR) in Micro, Small, and Medium Enterprises (MSMEs). The main focus of this study is to identify key elements, major challenges, and the role of financial factors in building supply chain resilience in MSMEs amid volatile conditions such as pandemics, economic crises, and digital disruptions. Research Design & Methods: This study uses a systematic literature review (SLR) approach with reference to the PRISMA protocol. The articles analyzed include 45 reputable international journals published between 2013 and 2024. The data were coded and analyzed using a thematic approach to group the dimensions of supply chain resilience relevant in the context of MSMEs. Findings: The analysis shows that the resilience of MSME supply chains is shaped by adaptive capabilities, organizational learning, the use of digital technology, and financing support. Financing plays a dual role as both a support and an obstacle; access to formal financing increases flexibility and risk mitigation strategies. Collaboration among SMEs and involvement in the local ecosystem also strengthen resilience. Key challenges include limited market information, reliance on single suppliers, and lack of readiness for digitalization. Implications & Recommendations: This study suggests that business policies and support should be designed according to the needs of MSMEs, including adaptive financing schemes and digital incubation programs. Strengthening digital financial literacy and integrating simple technology into supply chain management are key recommendations. Researchers are further advised to explore multi-level approaches involving external actors such as the government and financial institutions. Contribution & Value Added: This study enriches our understanding of MSME supply chain resilience by highlighting the role of financing and organizational learning, and offers a conceptual framework for further research and sustainable policy.